2002
DOI: 10.1002/bip.10096
|View full text |Cite
|
Sign up to set email alerts
|

Time‐resolved resonance Raman study on ultrafast structural relaxation and vibrational cooling of photodissociated carbonmonoxy myoglobin

Abstract: A localized small structural change is converted to a higher order conformational change of protein and extends to a mesoscopic scale to induce a physiological function. To understand such features of protein, ultrafast dynamics of myoglobin (Mb) following photolysis of carbon monoxide were investigated. Recent results are summarized here with a stress on structural and vibrational energy relaxation. The core expansion of heme takes place within 2 ps but the out of plane displacement of the heme iron and the a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
40
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(45 citation statements)
references
References 18 publications
(19 reference statements)
5
40
0
Order By: Relevance
“…This observation is consistent with spectroscopic investigations on WT MbCO (25) and time-resolved crystallographic studies on WT and mutant Mbs (7)(8)(9). In WT MbCO, the heme group relaxes within a time range spanning from hundreds of femtoseconds to a few picoseconds (45,46). L29W Mb is most likely similar in this respect.…”
Section: Events Faster Than Our Experimental Time Resolution: Subnanosupporting
confidence: 86%
“…This observation is consistent with spectroscopic investigations on WT MbCO (25) and time-resolved crystallographic studies on WT and mutant Mbs (7)(8)(9). In WT MbCO, the heme group relaxes within a time range spanning from hundreds of femtoseconds to a few picoseconds (45,46). L29W Mb is most likely similar in this respect.…”
Section: Events Faster Than Our Experimental Time Resolution: Subnanosupporting
confidence: 86%
“…The 8-ns photoproduct frequency for (Fe-His) from P-trHb-(CO) in solution at 220 cm Ϫ1 is consistent with full relaxation of the proximal environment within 8 ns, a result similar to what is observed for Mb (61,62). Under high viscosity conditions the frequency for the 8 ns photoproduct of P-trHb(CO) attains a value close to 230 cm Ϫ1 , characteristic of a proximal environment where the F-helix is in much closer proximity to the heme.…”
Section: A Kinetic Model For P-trhb and C-trhb-supporting
confidence: 81%
“…The slow component in their work (170-200 ps) was assigned to recombination of NO from the more distant Xe4 pocket (30). The rebinding occurs on a similar timescale as the structural fluctuations of the protein architecture (13,23,28,29), and therefore, relaxation of the active site after dissociation gives rise to a small time-dependent barrier (∼3 kJ mol −1 ) (17). From their mid-IR TA studies, Lim and coworkers (23,24) similarly concluded that the slow recombination component (133 ps in their case) is caused by the protein environment surrounding the distal side of the heme, and…”
mentioning
confidence: 99%
“…For UV-Vis and near-IR TA spectroscopy, the signals are dominated by the π-orbitals of the porphyrin, whereas mid-IR TA of the NO stretch mode is sensitive to the orientation of the NO dipole. Resonance Raman spectroscopy maps several vibrational modes of the porphyrin, but most studies have focused on the important Fe-N stretch vibration (at 220 cm −1 ) with the proximal histidine (20,(25)(26)(27), which is sensitive to the position of the iron atom out of the heme plane and to the strain that the protein exerts on the heme through movements of the helices (28,29).…”
mentioning
confidence: 99%